Experimental investigation of starting-up, energy-saving, and emission-reducing performances of hybrid supercapacitor energy storage systems for automobiles. (April 2023) - Zhang, Qinchao; Liu, Liangde; Zhang, Jiangyun; Zhang, Guoqing; Chen, Youpeng; Liu, Sizhi; Wu, Hongwei; Huang, Hongni
Abstract: Improvements in engine starting-up performance, such as reducing fuel consumption and exhaust emission pollution during the startup process, are very vital to achieve the national development goal of carbon peaking and carbon neutrality. Hybrid supercapacitor (HSC) energy storage systems containing batteries and supercapacitors (SCs) are considered promising energy storage strategies to compensate for the disadvantages of a single energy storage technology. In this paper, two kinds of novel 12 V/50 Ah and 12 V/70 Ah module-level energy storage systems composed of cell-level 3.6 V/2200 F HSCs were first designed. Analysis on their fundamental electrochemical properties under room temperature conditions was also performed. Four different types of energy storage systems composed of 12 V/70 Ah lithium iron phosphate (LFP) batteries, 12 V/70 Ah valve-regulated lead-acid (VRLA) batteries, and the aforementioned HSCs were then employed to compare their starting energy, energy-saving, and emission-reduction characteristics. Additionally, the 12 V/70 Ah HSC module saved 7.82 %, 3.18 %, and 1.65 % of fuel as compared to the 12 V/70 Ah VRLA, 12 V/70 Ah LFP, and 12 V/50 Ah HSC modules, respectively, demonstrating its superior fuel economy property. Simultaneously, the volume concentration of HC and CO emission in the startup process are 12.7 % and 13.2 % lower than that average of the other three modules, respectively, which shows a good exhaust emission reduction effect. The proposed energy storage system will provide systematic experimental data support and valuable theoretical guidance for the industrialization and application of HSCs. Highlights: Two HSC energy storage systems were independently designed and conducted. The starting-up, energy-saving, and emission-reducing performances of HSC energy storage systems were particularly analyzed. The 12 V/70 Ah HSC energy storage system showed an optimum environmental-friendly performance.